2019
DOI: 10.1002/stvr.1701
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the fitness function for the job: Automated generation of test suites that detect real faults

Abstract: Summary Search‐based unit test generation, if effective at fault detection, can lower the cost of testing. Such techniques rely on fitness functions to guide the search. Ultimately, such functions represent test goals that approximate—but do not ensure—fault detection. The need to rely on approximations leads to two questions—can fitness functions produce effective tests and, if so, which should be used to generate tests? To answer these questions, we have assessed the fault‐detection capabilities of unit test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…Finding new exceptions requires blind guessing. Past research showed that general functions such as Branch Coverage were able to trigger more exceptions simply by guiding the search to visit more of the codebase [73].…”
Section: Technical Approach and Implementationmentioning
confidence: 99%
“…Finding new exceptions requires blind guessing. Past research showed that general functions such as Branch Coverage were able to trigger more exceptions simply by guiding the search to visit more of the codebase [73].…”
Section: Technical Approach and Implementationmentioning
confidence: 99%
“…Dynamic method generates test data based on actual operation of the program, and the process is determinate [15]. This kind of methods need quite long time to generate test data, and is very sensitive to the initial test data [16]- [18].…”
Section: Related Workmentioning
confidence: 99%
“…This search can then be automated. Given a measurable goal, a metaheuristic optimization algorithm can systematically sample the space of possible test input and manipulate those samples, guided by feedback from one or more fitness functionsscoring functions that judge the optimality of the chosen input (Salahirad et al 2019). In other words: algorithm + fitness functions =⇒ goal.…”
Section: Introductionmentioning
confidence: 99%